Energy and nutritional value of biathletes' diets - R. M. Radzhabkadiev; A. N. Timonin; I. V. Kobelkova (Спортивная медицина: наука и практика, 2020)
Objective: evaluation of nutritional and energy value dietary intakes of elite athletes who engaged into biathlon. Materials and methods: 30 athletes (20 men and 10 women) were surveyed whose middle age was 20,9±0,75 и 19,4±0,5 years old, respectively. The studies were conducted in the immunology laboratory of Federal Researcher Centre of Nutrition and Biotechnology, and in the Federal Research and Clinical Center for Sports Medicine and Rehabilitation of the Federal Medical and Biological Agency of Russia. Study was conducted during pre-competition period, simultaneously with profound medical examination. Data collection of surveyed athletes' dietary intakes was carried out using questionnaire-polling method of 24-hour nutrition replication. The measure of consume food amounts was performed by using the «Servings album of products and dishes». The estimation of nutrients and energy consumption was carried out using an electronic database of the chemical composition of products and dishes. Results: estimation of the energy and nutritional value of the athletes diet has shown a discrepancy between the obtained values and the recommendations for this group of physical activity. Levels of diet's energy value amounted to 4043±230 (3732 – 4498 kcal/day) by men and 3479±156,4 (3228 – 3795 kcal/day) by women. The ratio of caloric intake of proteins, fats and carbohydrates in the diets of athletes was 14.5%, 37.3%, 48.1% for men, and 15.8%, 33.3% and 50.8% for women, respectively. In this, for athletes who generally train endurance the recommended ratio of protein, fat and carbohydrates in the diet is 13-15%, 24-25% and 58-61%, respectively according to various literary data. Conclusions: among surveyed athletes, there was a tendency towards exceed energy intake due to fat (37.3±2.7% in men; 33.3±2.5% in women) and insufficient carbohydrate intake (48.1±3.1% and 50, 8±2.3%, respectively) with normal levels of protein intake (14.5±1.3% for men; 15.8±2.3% for women). Despite the fact that women had a higher intake of carbohydrates than men, the proportion of complex carbohydrates in the structure of the diet was 7.5% lower (p <0.05). These findings indicate the diet imbalance of this athlete’s category.